2009
DOI: 10.1101/gad.1813709
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine signaling in a bacterium

Abstract: Cellular differentiation is triggered by extracellular signals that cause target cells to adopt a particular fate. Differentiation in bacteria typically involves autocrine signaling in which all cells in the population produce and respond to the same signal. Here we present evidence for paracrine signaling in bacterial populations-some cells produce a signal to which only certain target cells respond. Biofilm formation in Bacillus involves two centrally important signaling molecules, ComX and surfactin. ComX t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
268
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(283 citation statements)
references
References 41 publications
11
268
0
1
Order By: Relevance
“…In addition, we observed that a higher fraction of comQ cells activated srfA gene transcription in the presence of ComX than in the undomesticated QS + strains. Bimodal expression of srfA in undomesticated strains was reported previously (19) and was suggested to lead to phenotypic differentiation of the Bacillus population and a division of labor that provide fitness benefits (25). Our results show that the private link between signal production and QS response also has consequences for bimodal expression of srfA in the B. subtilis population.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In addition, we observed that a higher fraction of comQ cells activated srfA gene transcription in the presence of ComX than in the undomesticated QS + strains. Bimodal expression of srfA in undomesticated strains was reported previously (19) and was suggested to lead to phenotypic differentiation of the Bacillus population and a division of labor that provide fitness benefits (25). Our results show that the private link between signal production and QS response also has consequences for bimodal expression of srfA in the B. subtilis population.…”
Section: Discussionsupporting
confidence: 62%
“…3A) was comparable with that of the QS-proficient PS216, which is different from that of domesticated strains. Only PS216 produces surfactin and it was proposed recently that surfactin negatively regulates its own expression (19), which may explain the observed difference in the srfA-expression pattern between domesticated and PS216 derivatives. Interestingly, single-cell microscopy analysis revealed that, despite similar cumulative fluorescence of PS216 and the signal-deficient derivative PS216ΔcomQ in the presence of ComX, the distributions of srfA expression differed between the two strains: in PS216 30 ± 7% of cells did not express srfA-cfp regardless of ComX exposure, but only 14 ± 1% of the mutant population remained uninduced in the presence of ComX (Fig.…”
Section: Qs Signal Induces Dramatically Higher Surfactin Secretion Inmentioning
confidence: 97%
See 1 more Smart Citation
“…Surfactin production is triggered in a small subset of cells responding to another signalling molecule ComX, which is synthesized by most cells in the population. Surfactin then acts as a paracrine signal that leads to extracellular matrix production in a different subpopulation of cells, which can then no longer respond to ComX and therefore cannot became surfactin producers (Lopez et al, 2009d). The blockage of signalling molecules caused by the extracellular matrix has been reported in eukaryotes to define the distinct cell fates in morphogenesis.…”
Section: Biological and Physiological Relevance Of Surfactinmentioning
confidence: 99%
“…For instance, quorum sensing molecules secreted by various bacterial species serve as indicators of local population density and modulate coordinated responses (e.g., luminescence, virulence) in appropriate environmental conditions (4). Bacillus subtilus has also been shown recently to generate a paracrine signal, using the small molecule surfactin to induce differentiation of a subset of cells during biofilm formation (5).…”
mentioning
confidence: 99%